2022
DOI: 10.3221/igf-esis.63.23
|View full text |Cite
|
Sign up to set email alerts
|

The Metallurgical hydrogen as an indicator and cause of damage to rolled steel: Hydrogen diagnostics of fracture

Abstract: Fatigue tests and measurements of the volumetric distribution of metallurgical hydrogen in specimens cut from rolled I-beam 60Sh3 made of steel 10KhSND were carried out. Fatigue tests show a 20% reduction in fatigue limits compared to similar sheet material. On the fractures of the samples, there are flock-like defects in the areas of interface of the flanges of the I-beam, or the so-called zones of difficult deformation. The concentration of metallurgical hydrogen is unevenly distributed and varies from 0.17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…An economic analysis [2] of various transporting hydrogen fuel methods showed that the use of pipelines has the greatest potential in the long term compared to rail and road transport. The main problems of using the existing gas transportation system are the high ability of hydrogen to penetrate metal barriers [3] and the embrittlement of gas pipeline walls. However, the existing gas transportation system allows for the transportation of natural gas with a hydrogen content of up to 10%, with the prospect of increasing to 20% [4].…”
mentioning
confidence: 99%
“…An economic analysis [2] of various transporting hydrogen fuel methods showed that the use of pipelines has the greatest potential in the long term compared to rail and road transport. The main problems of using the existing gas transportation system are the high ability of hydrogen to penetrate metal barriers [3] and the embrittlement of gas pipeline walls. However, the existing gas transportation system allows for the transportation of natural gas with a hydrogen content of up to 10%, with the prospect of increasing to 20% [4].…”
mentioning
confidence: 99%